Chronic Alcohol Exposure Differentially Alters One‐Carbon Metabolism in Rat Liver and Brain. (25th April 2017) - Auta, James; Zhang, Huaibo; Pandey, Subhash C.; Guidotti, Alessandro
Abstract : Background: Epigenetic mechanisms such as DNA methylation play an important role in regulating the pathophysiology of alcoholism. Chronic alcohol exposure leads to behavioral changes as well as decreased expression of genes associated with synaptic plasticity. In the liver, it has been documented that chronic alcohol exposure impairs methionine synthase ( Ms ) activity leading to a decrease in S‐adenosyl methionine/S‐adenosyl homocysteine (SAM/SAH) ratio which results in DNA hypomethylation; however, it is not known whether similar alterations of SAM and SAH levels are also produced in brain. Methods: Male adult Sprague Dawley rats were fed chronically with Lieber–DeCarli ethanol (EtOH) (9% v/v) or control diet. The EtOH‐diet‐fed rats were withdrawn for 0 and 24 hours. The cerebellum and liver tissues were dissected and used to investigate changes in one‐carbon metabolism, SAM, and SAH levels. Results: We found that chronic EtOH exposure decreased SAM levels, SAM/SAH ratio, Ms, methylene tetrahydrofolate reductase, and betaine homocysteine methyltransferase ( Bhmt ) expression and increased methionine adenosyltransferase‐2b ( Mat2b ) but not Mat2a expression in the liver. In contrast, chronic EtOH exposure decreased SAH levels, increased SAM/SAH ratio and the expression of Mat2a and S‐adenosyl homocysteine hydrolase, while the levels of SAM or Bhmt expression in cerebellum remained unaltered. However, in both liver and cerebellum, chronic EtOH exposure decreased the expression of Ms and increased Mat2b expression. All chronic EtOH‐induced changes of one‐carbon metabolism in cerebellum, but not liver, returned to near‐normal levels during EtOH withdrawal. Conclusions: These results indicate a decreased "methylation index" in liver and an increased "methylation index" in cerebellum. The opposing changes of the "methylation index" suggest altered DNA methylation in liver and cerebellum, thus implicating one‐carbon metabolism in the pathophysiology of alcoholism. Abstract : Chronic ethanol exposure decreased SAM and SAH levels and SAM/SAH ratio in liver. However, in cerebellum the SAM levels did not change, while SAH levels decreased and SAM/SAH ratio increased. These results indicate a decrease and an increase of "methylation index" in liver and cerebellum respectively that may be associated with pathophysiology of alcoholism.